Construction of complex nested ideal lattices for complex-valued channel quantization - Watanabe, C.C. Trinca; Belfiore, J. C.; De Carvalho, E. D. [UNESP]; Filho, J. Vieira [UNESP]; Palazzo, R.; Watanabe, R. A. (Academic Publications, 2018)
In this work we develop a new algebraic methodology which quantizes complex-valued channels in order to realize interference alignment (IA) onto a complex ideal lattice. Also we make use of the minimum mean square error (MMSE) criterion to estimate complex-valued channels contaminated by additive Gaussian noise.
Keywords: Binary cyclotomic field; Channel quantization; Complex ideal lattices; Nested lattices; Principal ideal rings